2008
DOI: 10.1002/pola.23077
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and self‐assembly of ABA amphiphilic block copolymers containing styrene and oligo(ethylene glycol) methyl ether methacrylate in dilute aqueous solutions: Elevated cloud point temperatures for thermoresponsive micelles

Abstract: A series of ABA amphiphilic triblock copolymers possessing polystyrene (PS) central hydrophobic blocks, one group with “short” PS blocks (DP = 54–86) and one with “long” PS blocks (DP = 183–204) were synthesized by atom transfer radical polymerization. The outer hydrophilic blocks were various lengths of poly(oligoethylene glycol methyl ether) methacrylate, a comb‐like polymer. The critical aggregation concentrations were recorded for certain block copolymer samples and were found to be in the range circa 10−9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 105 publications
(119 reference statements)
3
35
3
Order By: Relevance
“…In pure water, the homo-polymers PMEO 2 MA and POEGMA 300 exhibited cloud points at 28 and 65 • C, respectively. These results are in good agreement with previously reported values [26,33]. Moreover, as expected, the cloud points of the co-polymers P(MEO 2 MA-co-OEGMA 300 ) in pure water were comprised in the temperature range 28-65 • C and closely depended on the composition of the co-polymers (i.e., on F OEGMA or f OEGMA ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In pure water, the homo-polymers PMEO 2 MA and POEGMA 300 exhibited cloud points at 28 and 65 • C, respectively. These results are in good agreement with previously reported values [26,33]. Moreover, as expected, the cloud points of the co-polymers P(MEO 2 MA-co-OEGMA 300 ) in pure water were comprised in the temperature range 28-65 • C and closely depended on the composition of the co-polymers (i.e., on F OEGMA or f OEGMA ).…”
Section: Resultssupporting
confidence: 82%
“…The homo-polymerization of the latter monomer has been already studied by various authors. For example, Holder and co-workers recently reported that homo-polymers POEGMA 300 exhibit reversible phase transitions in aqueous solution around 60-64 • C [33]. Additionally, Ishizone and co-workers studied the anionic polymerization of tetra(ethylene glycol) methyl ether methacrylate (i.e., MEO 4 MA, one of the main component of OEGMA 300 ) and obtained homo-polymers with a LCST of 68 • C [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, the chain length of the central PCL block was maintained constant and varied that of the terminal fragments. Diblock and triblock copolymers containing poly[oligo(ethylene glycol methyl ether) methacrylate] blocks have been synthesized previously 27,28 but not containing a central biodegradable block such as poly(e-caprolactone). Lately, with an increase in environmental awareness, amphiphilic biodegradable copolymers offer interesting properties for biotechnological applications.…”
mentioning
confidence: 99%
“…Access to well-defined, functional block copolymers has been dramatically improved over the past decade, with the advancement of controlled radical polymerization techniques (27)(28)(29)(30)(31)(32)(33). Although polyamides having primary amino side chain substituents have been prepared directly (34) by reversible addition-fragmentation chain transfer (35,36) radical polymerization, the amphiphilic block copolymer, poly(acrylamidoethylamine)-b-polystyrene (PAEA-b-PS) used in our studies, was obtained by amidation of a common block copolymer precursor for SCK construction, poly(acrylic acid)-b-polystyrene, by reaction with mono-Boc-protected 1,2-ethylene diamine and subsequent deprotection under standard conditions.…”
Section: Design Of Cationic Shell Crosslinked Nanoparticles For Delivmentioning
confidence: 99%